Multi-institutional profile of adults admitted to pediatric intensive care units - Edwards, Jeffrey D (2013)
IMPORTANCE: Growing numbers of persons with childhood-onset chronic illnesses are surviving to adulthood. Many use pediatric hospitals for their inpatient needs. To our knowledge, the prevalence and characteristics of adult pediatric intensive care unit patients have not been reported. OBJECTIVES: To estimate the proportion of adults admitted to pediatric intensive care units (PICUs), characterize them, and compare them with older adolescents. DESIGN: One-year cross-sectional analysis. SETTING: Pediatric intensive care units in the United States that participated in the Virtual Pediatric Intensive Care Unit Systems. PARTICIPANTS: Pediatric intensive care unit patients 15 years or older admitted in 2008. MAIN OUTCOME MEASURES: We compared adults with adolescents across clinical characteristics and outcomes. Mixed-effects logistic regression was used to estimate the independent association of age with PICU mortality. RESULTS: Seventy PICUs had 67 629 admissions; 1954 admissions (2.7%) were patients 19 years or older; and 9105 admissions (13.5%) were patients aged 15 to 18 years. The proportion of adults (_19 years) varied considerably by PICU (range, 0%–9.2%). As age increased, the proportion of patients who had a complex chronic condition and planned or perioperative admissions increased; the proportion of trauma-related admissions decreased. Patients aged 21 to 29 years had a 2 times (95% CI, 1.3–3.2; P=.004) greater odds of PICU mortality compared with adolescent patients, after adjusting for Paediatric Index of Mortality score, sex, trauma, and having a complex chronic condition. Being 30 years or older was associated with a 3.5 (95% CI, 1.3–9.7; P=.01) greater odds of mortality. CONCLUSIONS AND RELEVANCE: In this multi-institutional study, adults constituted a small but high risk proportion of patients in some PICUs, suggesting that these PICUs should have plans and protocols specifically focused on this group.